ANALISIS RESEPSI REMAJA KOTA SAMPIT MENGENAI KEBERAGAMAN DI MEDIA - Anastasia Yuni Widyaningrum; Mateus Yumarnamto; V Luluk Prijambodo (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
The aim of the study is to reveal the viewpoints of adolescents as media audiences, how they interpret their lives in the midst of Indonesia's diversity. The method used is Reception Analysis using encoding and decoding models from Stuart Hall. The subjects of the study were 9 Sampit City teenagers aged 15-18 years with a diversity of sex, religion, and ethnicity. While the concept used is the study of Indonesian-ness, imagined communities, nation and state and identity. The results showed that adolescents in Sampit City were traumatized by stories of riots based on ethnic sentiment as told by parents, based on YouTube's content and also through the context of the 2017 local election reporting. Ethnic sentiments still exist because the content on YouTube allows them to reconnect with the 2001 conflict. So the dominant meaning of hegemonic is that they agree that Indonesia's diverse ethnic situation can lead to conflict and is easily used by irresponsible groups. The next meaning on the negotiating side is that prejudice and stereotyping occur in Sampit, respectively. To eliminate the trauma of ethnic conflict, they hope that more activities will involve cultural gatherings.